Neighbourhood Watch Association: A Panacea to Crime Prevention and Management in Oyo State, Nigeria - Moses Igwe Bassey (Jurnal Administrasi Publik (Public Administration Journal), 2023)
Crime and other form of insecurity is one of the greatest threats facing Nigeria’s State today. The different measures put in place by the government to manage it have not achieved the desired outcome; thereby resulting in communities setting up Neighbourhood Watch Association (NWA) policing strategy as a self-help measure to secure their environment. This study investigated NWA as a community policing initiative in Oyo State, South/West, Nigeria. The research design adopted was the descriptive survey; the sample population of the study was drawn from 10 LGAs using an accidental sampling technique. The study also used both primary and secondary sources of data. The Primary sources were 7 In-depth Interviews (IDI) conducted and 104 copies of the questionnaire administered to respondents. The secondary sources of data were books, journals, online materials, articles, and some magazines published by various scholars on the subject matter. The findings from the study revealed that the NWA policing strategy has been very effective in preventing petty crimes such as theft, land disputes, burglary, and armed robbery.  However, it has not been able to prevent crimes like kidnap, land disputes, and farmer/herders’ conflict which is very common in different parts of Oyo State. The study therefore concluded that NWA is very useful in crime prevention and management strategy. However, the government should address the root causes of insecurity in the state, and members of NWA should be well-trained to avoid jungle justice presently meted out to suspected criminals.